(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Abstract: Accounting is an important system that serves to fully, accurately and systematically reflect the financial activities of an enterprise. In a market economy, the role and tasks of accounting expand significantly, since Enterprises independently conduct their activities, enter into competition and strive to ensure financial stability. Therefore, the adaptation of accounting to the requirements of a market economy is not only a necessity, but also a key factor in the successful functioning of the enterprise.